Synthesis and Herbicidal Activity of Novel 4‐Acyl‐2, 5‐disubstituted‐3‐hydroxypyrazoles and 4‐Arylcarbonyl‐3‐substitutedisoxazol‐5‐ones. (13th September 2013) - Song, Hong; Feng, Wei‐Bing; Cheng, Feng; Shi, De‐Qing
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>